Post-traumatic pseudoaneurysm of the descending aorta - Izadmehr Ahmadinejad; Mojtaba Ahmadinejad; Ali Soltanian; Yasmina Ahmadinejad; Alireza Shirzadi; Pouria Chaghamirzayi (Trauma Case Reports)
High-energy deceleration injuries of the thoracic aorta are associated with high mortality. But among long term survivors, just 2 %–5 % of traumatic aortic injuries fail initial detection and are discovered later (Pozek et al., 2012 [1]). We present a rare case of pseudoaneurysm of the descending aorta in a female with a history of chest blunt trauma 45 days before who presented with chronic severe cough and vocal hoarseness that was treated with endovascular intervention in our center.